(untitled) (Universitas Scientiarum, 2011)
Objective. To identify the cultivated and wild species of Rubus in 53 farms with commercial plantations of Rubus glaucus Benth, owned by four blackberry grower associations in the towns of Pamplona and Chitagá, (Norte de Santander, Colombia). Materials and methods. Three to five specimens were collected from each farm and along the roadside. Plants aged 9 to 12 months since their plantation in the commercial farms and wild materials with characteristics of Rubus were selected. Twenty two descriptors (fourteen quantitative and eight qualitative) were assessed. We considered the seventh and eighth branch buds both male and female (with five repetitions) and fruits and flowers of each material. Principal component analysis was done with the fourteen quantitative variables, to identify the descriptors that most contribute to the morphological differentiation of accessions. A conglomerate analysis was used for grouping accessions according to their similarity and dissimilarity. Results. Among the 147 accessions analyzed from the different farms, our study determined the presence of 6 different taxa: R. glaucus Benth (with and without spines), R. alpinus Macfad, R. adenotrichos Schltdl, R. rosifolius Sm., R. bogotensis Kunth and R. floribundus Kunth Conclusions. The descriptors that differentiated the species and discriminated them by groups by providing 77% of the information with the use of principal component analysis, were: length and width of central and lateral leaflets, length of flower and leaf structures, apex shape and number of secondary veins. Key words: Rubus glaucus Benth, identification, taxa, descriptors, principal component analysis, conglomerate analysis